2021
DOI: 10.29303/jbt.v21i3.2907
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heavy Metal Content of Copper (Cu) in Milkfish (Chanos chanos Forsk) from Milkfish Farms in Bima Bay 2020

Abstract: Fish are aquatic organisms and are often used as biological indicators of heavy metals in waters, because fish belong to the highest trophic level and their nature is to settle in certain habitats. This research aims to explore the Cu content in milkfish from the Bima Bay milkfish aquaculture to determine the copper content in milkfish from the Bima Bay milkfish aquaculture. The usefulness of this research is to provide information on the Cu content of milkfish aquaculture in Bima Bay. This research was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
0
0
2
Order By: Relevance
“…On rice snails obtained from rice fields in the Rancaekek District area that Cu levels in each sample of rice snails (65.7 mm/kg, 3.5 mm/kg, 6.2 mm/kg, 5 mm/kg, 5.8 mm/kg, 6.2 mm/kg, and 4.9 mm/kg) did not exceed the maximum threshold for metal contamination in a food regulated by the Decree of the Director General of Drug and Food Control No.03725/B/SK/VII/1989) and also safe for daily consumption with a consumption limit of no more than one kilogram per day [11]. Similar results are also in line with [28] research but in different aquatic biota; it was found that there was a heavy metal Cu content in milkfish flesh of 0.621 mg/kg from Bima Bay milkfish farms. The Cu content is still below the threshold according to the Director General of POM Decree No.03725/B/SK/VII/89, which is 20.0 mg/kg.…”
Section: Resultssupporting
confidence: 79%
“…On rice snails obtained from rice fields in the Rancaekek District area that Cu levels in each sample of rice snails (65.7 mm/kg, 3.5 mm/kg, 6.2 mm/kg, 5 mm/kg, 5.8 mm/kg, 6.2 mm/kg, and 4.9 mm/kg) did not exceed the maximum threshold for metal contamination in a food regulated by the Decree of the Director General of Drug and Food Control No.03725/B/SK/VII/1989) and also safe for daily consumption with a consumption limit of no more than one kilogram per day [11]. Similar results are also in line with [28] research but in different aquatic biota; it was found that there was a heavy metal Cu content in milkfish flesh of 0.621 mg/kg from Bima Bay milkfish farms. The Cu content is still below the threshold according to the Director General of POM Decree No.03725/B/SK/VII/89, which is 20.0 mg/kg.…”
Section: Resultssupporting
confidence: 79%
“…Ikan adalah hewan air yang mempunyai pergerakan cepat sehingga dapat terhindar dari pencemaran, namun pergerakannya terbatas pada habitat tertutup seperti danau (Yusuf et al, 2013). Ikan sering digunakan sebagai indikator biologis logam berat (Yunanmalifah et al, 2021). Jenis ikan yang digunakan sebagai bioindikator adalah ikan mujair.…”
Section: Pendahuluanunclassified
“…Ikan dalam rantai makanan di suatu perairan air dapat mengakumulasi logam dari lingkungannya. Apabila ikan yang terakumulasi logam berat dikonsumsi oleh manusia, hal itu dapat berbahaya bagi kesehatan (Cahyani et al, 2016;Yunanmalifah et al, 2021). Ikan yang hidup di danau lebih mudah terkontaminasi oleh logam berat dibandingkan dengan ikan yang hidup di perairan terbuka dikarenakan danau adalah habitat yang terbatas sehingga lebih mudah untuk terkontaminasi (Kahiruddin et al, 2021).…”
Section: Pendahuluanunclassified